Non-ischemic Heart Preservation via Hypothermic Cardioplegic Perfusion Induces Immunodepletion of Donor Hearts Resulting in Diminished Graft Infiltration Following Transplantation - Critchley, William R.; Stone, John P.; Liao, Qiuming; Qin, Guangqi; Risnes, Ivar; Trafford, Andrew; Scott, Helge; Sjöberg, Trygve; Steen, Stig; Fildes, James E. (Frontiers in Immunology, 2020)
Introduction: Many donor organs contain significant leukocyte reservoirs which upon transplantation activate recipient leukocytes to initiate acute rejection. We aimed to assess whether ex vivo heart perfusion promotes immunodepletion and alters the inflammatory status of the donor organ prior to transplantation. Methods: Isolated porcine hearts underwent ex vivo hypothermic, cardioplegic perfusion for 8 hours. Leukocyte populations were quantified in left ventricle samples by flow cytometry. Cell-free DNA, cytokines and chemokines were quantified in the perfusate. Tissue integrity was profiled by targeted proteomics and a histological assessment was performed. Heterotopic transplants comparing ex vivo hypothermic preservation and static cold storage were utilised to assess graft infiltration as a solid clinical endpoint. Results: Ex vivo perfusion significantly immunodepleted myocardial tissue. The perfusate displayed a selective, pro-inflammatory cytokine/chemokine pattern dominated by IFN-γ. The tissue molecular profile was improved following perfusion by diminished expression of 9 pro-apoptotic and 6 ischaemia-associated proteins. Histologically, no evidence of tissue damage was observed and cardiac troponin I was low throughout perfusion. Cell-free DNA was detected, the source of which may be necrotic/apoptotic leukocytes. Post-transplant graft infiltration was markedly reduced in terms of both leucocyte distribution and intensity of foci. Conclusions: These findings demonstrate that ex vivo perfusion significantly reduced donor heart immunogenicity via loss of resident leukocytes. Despite the pro-inflammatory cytokine pattern observed, a pro-survival and reduced ischaemia-related profile was observed, indicating an improvement in graft viability by perfusion. Diminished graft infiltration was observed in perfused hearts compared with those preserved by static cold storage following 48hrs of transplantation.